Fracture of abutment screw supporting a cemented implant-retained prosthesis with external hexagon connection: a case report with sem evaluation - Mariana Diniz Bisi Santos; Arthur Braga Pfeifer; Marcos Rogério Pupo Silva; Claudio Luiz Sendyk; Wilson Roberto Sendyk (University of São Paulo, 2007)
One of the causes of implant failures in cemented implant-retained prostheses is the fracture of abutment screw or UCLA abutment. This article reports a case of simultaneous fracture of two UCLA abutments screws occurring in an implant-supported prosthesis placed in the mandibular molar region. The fractured structures were examined under scanning electron microscopy to investigate the probable causes of the failure, which were not related to failures on materials or fabrication of the screws, but rather were due to shear forces. The misfit in cemented prostheses may be the most likely cause of shear force generation.